Poster #21 - Development and use of mobile application for transboundary animal and emerging zoonotic diseases surveillance – a One Health project for improving human, animal health and food security in Vietnam - Thang Nguyen-Tien; Hu Suk Lee; Park, M.; Luong Hung Nam; Sinh Dang-Xuan; Unger, Fred; Hung Nguyen-Viet (Elsevier, 2025)
Background: Vietnam has been identified as a “hotspot” for Transboundary Animal and Emerging Zoonotic Diseases (TAEZDs) in South East Asia. In the framework of the “Improving human health through sustainable value chains in human-animal-environmental interactions using ICT in Vietnam (ICT4HEALTH)” project funded by Korean Ministry of Agriculture, Food, and Rural Affairs, we developed and used a mobile application, named Farmvetcare, to improve the timeliness and accuracy of surveillance and response to TAEZDs in two pilot provinces (Hoa Binh and Lao Cai) in Vietnam.